Towards a Sociopolitical Aesthetics of Smell - Elena Mancioppi (Rivista di Estetica, 2021)
The relationship between smell and politics could appear obscure; and yet, when it comes to smell, questions about freedom and constriction, social and ontological mingling or distinctions, clearly arise. In this paper, I will especially focus on the domain of food as a clear example for describing some of the political ambivalences characterizing the sense of smell. The aim is to pave the way for a more detailed ‘sociopolitical aesthetics of smell’ to come. I will stress epistemological and social features of odors in order to highlight their ambivalence in knowledge and community life. Perceivers and odors will emerge as mingled bodies, highlighting an ongoing process of material as well as emotional affection. Moreover, I will present some relevant examples of smell as social status symbols in relation to the aesthetic values linked to class hierarchy. Consumerism and scented goods will be lastly discussed in order to shade light on contemporary perceptual phenomena and their role in the socioeconomic dimension.